The potential supply risk of vanadium for the renewable energy transition in Germany. (January 2021) - Ciotola, Angela; Fuss, Maryegli; Colombo, Simone; Poganietz, Witold-Roger
Highlights: VRFBs have chances to become globally interesting due to their advantages. Four stochastic models analyze different adoption shares of VRFBs. 32 indexes were correlated to assess the risks associated with vanadium and VRBs. The lowest risk is the adoption of 50% VRFBs with Germany as a producer. The mining and refining processes are the riskiest activities for vanadium supply. Abstract: Vanadium-based Redox Flow Batteries (VRFBs) seem to be a promising solution for medium and large storage systems required to smooth the fluctuating provision of solar and wind energy. Beside technological considerations, the challenge for VRFBs is the availability of vanadium, influenced by the high demand by the steel and chemical sectors and the small number of mines operating worldwide. Given vanadium's toxicity, the health, safety, and environmental (HSE) implications might, too, affect vanadium's availability. This study assesses the risks of supply disruptions associated with vanadium for VRFBs for the German market through the Holistic Risk Analysis and Modelling (HoRAM) method. The analysis includes not only technological parameters but also HSE and societal ones. In total, 242 variables were selected to characterize vanadium's supply chain. Considering a successful energy transformation in 2050, four logic-stochastic models were created to assess the supply risks associated with four different market shares of VRFBs at the storage market, i.e. 10%, 25%, 50%, and 100%. The most crucial factor influencing the overall risk of supply turned out to be mining activities. These are driven by a lack of qualified personnel, but the HSE and societal aspects can also hamper the supply chain. Therefore, both the Government and companies should consider these aspects to better orientate their future strategies. Of the four analysed market shares, surprisingly the 50% one has shown the lowest risk. Further, the mitigation strategy of opening the domestic market could reduce the risk of vanadium supply disruption, i.e. high impacts for VRFBs.